From Citizen Science to DIY Science - Nascimento, S.; Angela Pereira; Ghezzi, A. (OuiShare Fest, 2015)
The number of projects that invite citizens into the scientific endeavour has been growing rapidly, described as citizen science. However, most of the times citizens are being limited to engage as data collectors or resources suppliers for projects that originate in the scientific community or led by institutions, such as universities or research centers, which don’t necessarily address the questions of individuals or from society. We will look into further developments of citizen and DIY science as deeper forms of engagement with techno-science. DIY scientists appear as people who tinker, hack, fix, recreate and assemble objects and systems in creative and unexpected directions, responding to individual or community-based questions, usually adhering to open paradigms to share knowledge and outputs with others. We will explore how DIY science is recognizing different ways of knowing and thus allowing for more out-of-the-box thinking and experimentation, or more generally, how it is changing knowledge production, citizen agency and ultimately innovation and creativity, or the meaning of ‘science’.